Combined Targeted and Untargeted Profiling of HeLa Cells Deficient in Purine De Novo Synthesis - Mádrová, Lucie; Součková, Olga; Brumarová, Radana; Dobešová, Dana; Václavík, Jan; Kouřil, Štěpán; de Sousa, Julie; Friedecká, Jaroslava; Friedecký, David; Barešová, Veronika; Zikánová, Marie; Adam, Tomáš (Metabolites, 2022)
Three genetically determined enzyme defects of purine de novo synthesis (PDNS) have been identified so far in humans: adenylosuccinate lyase (ADSL) deficiency, 5-amino-4-imidazole carboxamide-ribosiduria (AICA-ribosiduria), and deficiency in bifunctional enzyme phosphoribosylaminoimidazole carboxylase and phosphoribosylaminoimidazolesuccinocarboxamide synthase (PAICS). Clinical signs of these defects are mainly neurological, such as seizures, psychomotor retardation, epilepsy, autistic features, etc. This work aims to describe the metabolic changes of CRISPR-Cas9 genome-edited HeLa cells deficient in the individual steps of PDNS to better understand known and potential defects of the pathway in humans. High-performance liquid chromatography coupled with mass spectrometry was used for both targeted and untargeted metabolomic analyses. The statistically significant features from the untargeted study were identified by fragmentation analysis. Data from the targeted analysis were processed in Cytoscape software to visualize the most affected metabolic pathways. Statistical significance of PDNS intermediates preceding deficient enzymes was the highest (p-values 10 × 10-7-10 × 10-15) in comparison with the metabolites from other pathways (p-values of up to 10 × 10-7). Disturbed PDNS resulted in an altered pool of adenine and guanine nucleotides. However, the adenylate energy charge was not different from controls. Different profiles of acylcarnitines observed among deficient cell lines might be associated with a specific enzyme deficiency rather than global changes related to the PDNS pathway. Changes detected in one-carbon metabolism might reduce the methylation activity of the deficient cells, thus affecting the modification state of DNA, RNA, and proteins.
Keywords: metabolomics; HeLa cells; mass spectrometry; purine de novo synthesis; rare metabolic disorders